Marital communication skills training to promote marital satisfaction and psychological health during pregnancy: a couple focused approach - Zahra Alipour; Ashraf Kazemi; Gholamreza Kheirabadi; Ahmad-Ali Eslami (BMC, 2020)
Abstract Background Studies showed that decreased marital satisfaction and increased risk of depression and anxiety were mutually related. Therefore, this study was conducted to evaluate the effect of communication skills training with a couple focused approach on marital satisfaction and psychological symptoms among pregnant women. Methods This experimental study was performed on 60 pregnant women with low marital satisfaction who were divided into two groups of intervention and control. The women in the intervention group and their husbands participated in a communication training program based on the couple focused approach. The levels of anxiety, depression, and marital satisfaction were evaluated before and then one and three months after the intervention using valid questionnaires. Results The results indicated that after the intervention, compared to the pre-intervention period, the levels of marital satisfaction increased while the levels of depression and anxiety decreased significantly in the intervention group (p < 0.05). The comparison of the groups revealed significant differences in the scores of marital satisfaction, depression, and anxiety in the intervention and control groups at the intervals of one month and three months after the intervention (p < 0.05). Conclusions The research findings indicated that communication skills training program based on the couple focused approach and an emphasis on the needs of pregnant women during the pregnancy can improve the marital satisfaction and psychological health of pregnant women. Trial registration Iranian Registry of Clinical Trials IRCT2017012932264N2, Date of registration: 2017-06-28 Retrospectively registered.